The Conservation Balancing Act: Leader's Guide - Virginia Peart (EDIS)
This program will provide the participant with an understanding of how to conserve water and energy without sacrificing benefits in three major water using areas of the home: the bathroom, the laundry, and the kitchen.  This document is FCS 3231, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: February 2003. First published: September 1994. Revised: February 2003.